Optimasi Nitrogen dan Kerapatan Tanaman Terhadap Produktivitas Kangkung Darat (Ipomoea reptans Poir): Optimasi Nitrogen dan Kerapatan Tanaman Terhadap Produktivitas Kangkung Darat (Ipomoea reptans Poir) - Setyo Utomo, Pamuji; Mustopa, Tarwa; Helilusiatiningsih, Nunuk (Fakultas Pertanian UTP, 2026)
Land spinach (Ipomoea reptans Poir.) is an economically important leafy vegetable widely consumed in Indonesia due to its high nutritional value, including vitamins, minerals, dietary fiber, and bioactive compounds beneficial to human health. The increasing demand for fresh vegetables has encouraged efforts to improve land spinach productivity. However, productivity at the farm level remains suboptimal, partly due to inappropriate nitrogen fertilization and plant density management. Nitrogen is a key nutrient regulating vegetative growth, while plant density determines the level of competition for light, water, nutrients, and growing space. This study aimed to evaluate the effects of nitrogen application rates, plant density, and their interaction on the growth and productivity of land spinach. The hypothesis proposed that increasing nitrogen rates combined with appropriate plant density would enhance plant growth and productivity, and that a significant interaction exists between both factors. The experiment was conducted in Tanon Village, Papar District, Kediri Regency, Indonesia, from October to November 2025 using a factorial Randomized Complete Block Design (RCBD) with three replications. The first factor consisted of three urea application rates (300, 400, and 500 kg ha?¹), while the second factor consisted of three plant densities (4, 5, and 6 seeds per planting hole). Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% significance level. The results showed that nitrogen application significantly affected plant height, leaf number, leaf area, fresh weight per plant, and fresh weight per plot. Plant density also significantly influenced most growth and yield variables. A significant interaction between nitrogen rate and plant density was observed for leaf area, fresh weight per plant, and fresh weight per plot. The combination of 500 kg urea ha?¹ and 4 seeds per planting hole produced the highest fresh weight per plant (67.68 g plant?¹), whereas the combination of 500 kg urea ha?¹ and 6 seeds per planting hole resulted in the highest productivity (9.98 kg plot?¹ or approximately 49.9 t ha?¹). It can be concluded that increasing nitrogen application up to 500 kg ha?¹ combined with appropriate plant density management effectively enhances the growth and productivity of land spinach. For maximizing yield per unit area, the combination of 500 kg urea ha?¹ and 6 seeds per planting hole is recommended.